2017
DOI: 10.1136/bmjopen-2017-017198
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcomes of vaginal breech delivery for singleton term pregnancies in a carefully selected Cameroonian population: a cohort study

Abstract: Background and objectivesVaginal breech delivery (VBD) is known to be associated with more perinatal and maternal complications. Very few studies on the subject have been carried out in poor-resource settings. The aim of this study was to determine maternal and neonatal outcomes in carefully selected cases of VBD for singleton term pregnancies in a tertiary centre in Cameroon.DesignA retrospective cohort study.SettingA tertiary hospital in Yaounde, Cameroon.ParticipantsCases of VBD of newborns weighing 2500–35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
4
9
0
Order By: Relevance
“…Although the exact cause of this MSAF is unclear, fetal distress, cord accidents and maternal hypertension have been identified as potential risk factors [9] [10]. Intrauterine emission of meconium has both fetal and neonatal consequences as well as maternal risks [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact cause of this MSAF is unclear, fetal distress, cord accidents and maternal hypertension have been identified as potential risk factors [9] [10]. Intrauterine emission of meconium has both fetal and neonatal consequences as well as maternal risks [5].…”
Section: Introductionmentioning
confidence: 99%
“…This shows that vaginal breech deliveries are associated with adverse fetal outcomes. 1,5,6 There were no major maternal complications.…”
Section: Discussionmentioning
confidence: 86%
“…In two studies in Sub-Saharan countries, there was a strong association between vaginal breech delivery of singleton term pregnancies and maternofetal morbidity, with newborns more likely to suffer from birth asphyxia. 5,6 In a Saudi Arabian study, there was higher neonatal mortality found in vaginal breech delivery for singleton preterm breech fetus. 7 Vaginal breech delivery is still a safe option without compromising maternal and neonatal outcome if strict criteria are met before and during labour.…”
Section: Introductionmentioning
confidence: 98%
“…In some studies, occupation of the women could not be clearly defined as there could be combinations of occupations, for instance a housewife being unemployed, an entrepreneur or a peasant [18]. Parity was found to be associated with stillbirths, abruptio placentae, LBW, placental abnormalities, hypertension and eclampsia [14,16,[20][21][22]27,[31][32][33][34][35]. High parity presents as a risk factor due to the characteristics of multiparous women, which include high tendencies of performing unsupervised vaginal deliveries, not seeking antenatal care and their advanced age [22].…”
Section: Resultsmentioning
confidence: 99%